Some Results of the Joint Research of the M. Nodia Institute of Geophysics, TSU and Institute of Hydrometeorology, GTU from 2019 to 2023 and Prospects for their Further Development - Varamashvili, Nodar D.; Pipia, Mikheil G. (Journals of Georgian Geophysical Society, 2024)
A brief information on joint research of the M. Nodia Institute of Geophysics, TSU and the Institute of Hydrometeorology, GTU, conducted in 2019–2023 and the prospects for their further development are presented.